2013
DOI: 10.4137/jcm.s11276
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Complicated by Cervical Varix and Low-Lying Placenta: A Case Report

Abstract: We present a case of cervical varix and low-lying placenta. A cesarean section was performed because of the risk of bleeding with vaginal delivery; hemostasis was achieved using z sutures at the bleeding points. After delivery, the cervical varix decreased dramatically in size. It is important to recognize the clinical features and available treatments for cervical varix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…It emphasized that pregnant women with a prior cesarean should receive appropriate counseling concerning VBAC versus elective repeat cesarean in order to make an informed decision. This counseling would presumably include individualized risk-benefit assessment of trial of labor with likelihood of successful VBAC [7,8,9,10]…”
Section: Introductionmentioning
confidence: 99%
“…It emphasized that pregnant women with a prior cesarean should receive appropriate counseling concerning VBAC versus elective repeat cesarean in order to make an informed decision. This counseling would presumably include individualized risk-benefit assessment of trial of labor with likelihood of successful VBAC [7,8,9,10]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the development of cervical varix is associated with abnormal placentation. A PubMed database search found that 6 of the 11 reported cases of cervical varix were accompanied by placenta previa or a low-lying placenta [678]. Most patients in these cases were diagnosed in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical varicosities, however, are rare and have been associated with significant risk of hemorrhage. Most reported cases have resulted in delivery due to hemorrhage during the second or third trimester [3][4][5][6][7][8][9][10][11]. Cervical varicosities diagnosed during pregnancy have been associated with maternal in utero exposure to diethylstilbestrol, Klippel-Trenaunay syndrome, and abnormal placentation [3,[7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%